Social Disadvantage and Crime: A Criminological Puzzle. (September 2016) - Wikström, Per-Olof H.; Treiber, Kyle
In this article, we analyze the relationship between social disadvantage and crime, starting from the paradox that most persistent offenders come from disadvantaged backgrounds, but most people from disadvantaged backgrounds do not become persistent offenders. We argue that despite the fact that social disadvantage has been a key criminological topic for some time, the mechanisms which link it to offending remain poorly specified. Drawing on situational action theory, we suggest social disadvantage is linked to crime because more people from disadvantaged versus affluent backgrounds develop a high crime propensity and are exposed to criminogenic contexts, and the reason for this is that processes of social and self-selection place the former more frequently in (developmental and action) contexts conducive to the development and expression of high crime propensities. This article will explore this hypothesis through a series of analyses using data from the Peterborough Adolescent and Young Adult Development Study (PADS+), a longitudinal study which uses a range of data collection methods to study the interaction between personal characteristics and social environments. It pays particular attention to the macro-to-micro processes behind the intersection of people with certain characteristics and environments with certain features – i.e., their exposure – which leads to their interaction.